REAL TIME TORQUE & EFFICIENCY MONITORING OF INDUCATION MOTOR BY USING WIRELESS SENSOR NETWORK: A REVIEW - Snehal P. Jadhav, Vikram A. Mane (International Journal of Research Science and Management, 2014)
The system proposed in this paper aims at monitoring the torque and efficiency in induction motors in real time by employing wireless sensor networks (WSNs). An embedded system is employed for acquiring electrical signals from the motor in a noninvasive manner, and then performing local processing for torque and efficiency estimation. The values calculated by the embedded system are transmitted to a monitoring unit through an IEEE 802.15.4-based WSN. At the base unit, various motors can be monitored in real time. The embedded system was deployed on a workbench, and studies were conducted to analyze torque and system efficiency.